Shaping flood risk governance through science-policy interfaces: Insights from England, France and the Netherlands. Issue 106 (April 2020) - Hegger, Dries; Alexander, Meghan; Raadgever, Tom; Priest, Sally; Bruzzone, Silvia
Highlights: We develop a framework for analysing the role of Science Policy Interfaces in Flood Risk Governance. We apply this framework to England, France and the Netherlands using policy analysis and stakeholder interviews. SPIs help diversify FRM; increase their connectivity, facilitate decentralisation of FRM and foster inter-country learning. SPIs can steer FRG, either along existing pathways, or towards new and potentially transformative change. SPIs are an underexposed factor explaining dynamics in flood risk governance which merits more systematic empirical study. Abstract: In the face of increasing threats from flooding, there are growing calls to strengthen and improve arrangements of flood risk governance (FRG). This endeavour requires an appreciation of the multitude of factors stabilising and driving governance dynamics. So-called catalyst flood events, policy champions and advocacy coalitions have tended to dominate this study to date, whilst the potential role played by Science Policy Interfaces (SPIs) has been somewhat neglected and often approached in a reductionist and fragmented way. This paper addresses this gap by drawing from in-depth policy analysis and stakeholder interviews conducted within England, France and the Netherlands under the auspices of the EU-FP7 STAR-FLOOD project. The analysis reveals four prominent ways in which SPIs shape FRG, by i) facilitating the diversification of Flood Risk Management (FRM) strategies; ii) increasing their connectivity, iii) facilitating a decentralisation of FRM and iv) fostering inter-country learning. It identifies different roles of specific interfaces (structures) and interfacing mechanisms (processes) in shaping governance dynamics. This way, the analysis reveals various 'entry points' through which SPIs can steer FRG, either along existing pathways, or towards new and potentially transformative change. The study shows that SPIs are a hitherto underexposed factor explaining dynamics in flood risk governance which merits additional systematic empirical study.